Subsurface anatomy of the Irazú–Turrialba volcanic complex, inferred from the integration of local and ambient seismic tomographic methods - Jiwani Brown, Elliot Amir (2024)
Irazú and Turrialba are a twin volcanic complex that marks a distinct stop in volcanism along the Central America volcanic arc. We present a new traveltime velocity model of the crust beneath Iraz ´ u and Turrialba volcanoes, Costa Rica, and interpret it considering the results of previous ambient noise tomographic inversions. Data were acquired by a temporary seismic network during a period of low activity of the Iraz ´ u–Turrialba volcanic complex in 2018–2019. Beneath the Iraz ´ u volcano, we observe low P -wave velocities ( V P = 5 km s −1 ) and low velocity ratios ( V P / V S = 1.6). In contrast, below the Turrialba volcano, we observe low S -wav e v elocities ( V S = 3 km s −1 ) and a high V P / V S ( = 1.85) anomaly. We found that locations of low V P and V S anomalies ( −15 %) correspond well with shear wave velocity anomalies retrieved from ambient noise tomography. At shallower depths, we observe high V P and V S anomalies ( + 15 %) located between the summits of the volcanoes. Subvertical velocity anomalies are also observed at greater depths, with high V P and V S anomalies appearing at the lower limits of our models. We propose a complex structure of an intermediate magmatic reservoir, presenting multiphase fluid states of a liquid-to-gas transition beneath Iraz ´ u and a juvenile store of magmatic fluid beneath Turrialba, while shallow fluid transport provides evidence of magmatic–hydrothermal interactions.